Guest Editor: G. Castaman GENE THERAPY FOR HEMOPHILIA: FACTS AND QUANDARIES IN THE 21ST CENTURY - Bhavya S Doshi; Valder R Arruda; Valder R Arruda (Mediterranean Journal of Hematology and Infectious Diseases)
Therapy for hemophilia has evolved in the last 40 years from plasma-based concentrates to recombinant proteins and, more recently, to non-factor therapeutics. Along this same timeline, research in adeno-associated virus (AAV) based gene therapy vectors has provided the framework for successful early phase clinical trials initially for hemophilia B (HB) and now for hemophilia A. Successive lessons learned from these early pivotal HB trials have paved the way for current advanced phase trials. Nevertheless, questions linger regarding 1) the optimal balance of vector dose to transgene expression, 2) amount and durability of transgene expression required, and 3) long-term safety. Some trials have demonstrated unique findings not seen previously regarding transient elevation of liver enzymes, immunogenicity of the vector capsid, and loss of transgene expression. This review will provide an update on the clinical AAV gene therapy trials in hemophilia and address the questions above. A thoughtful and rationally approached expansion of gene therapy to the clinics would certainly be a welcome addition to the arsenal of options for hemophilia therapy. Further, the global impact of gene therapy could be vastly improved by expanding eligibility to different patient populations and to developing nations. With the advances made to date, it is possible to envision a shift from the early modest goal of simply increasing life expectancy to a significant improvement in quality of life by reduction in spontaneous bleeding episodes and disease complications.